2014
DOI: 10.1377/hlthaff.2013.1119
|View full text |Cite
|
Sign up to set email alerts
|

What The Affordable Care Act Means For People With Jail Stays

Abstract: About one in six people expected to enroll in Medicaid under health reform expansions and nearly one in ten expected to enroll in qualified health plans through the health insurance Marketplaces will have spent some time in jail during the past year. People who have spent time in jail frequently cycle in and out of incarceration; have high rates of chronic physical, mental health, and substance use conditions; and historically have been uninsured and without access to continuous health care. The Affordable Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…[4][5][6][7] Yet, treatment among individuals with recent justice involvement has historically been inadequate due to lack of health insurance coverage [8][9][10] and other barriers to care, including troubles navigating the healthcare system post release, 11 disruption of medication during incarceration, 12 and lack of behavioral health services. 13 Roughly half of justice-involved individuals are expected to be eligible for health insurance through the Affordable Care Act (ACA), 10,14 and many believe insurance expansion offers an opportunity to improve access to substance abuse and mental health treatment for this population. 5,14,15 One recent report suggested that the ACA improved insurance rates among justice-involved individuals with SUD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7] Yet, treatment among individuals with recent justice involvement has historically been inadequate due to lack of health insurance coverage [8][9][10] and other barriers to care, including troubles navigating the healthcare system post release, 11 disruption of medication during incarceration, 12 and lack of behavioral health services. 13 Roughly half of justice-involved individuals are expected to be eligible for health insurance through the Affordable Care Act (ACA), 10,14 and many believe insurance expansion offers an opportunity to improve access to substance abuse and mental health treatment for this population. 5,14,15 One recent report suggested that the ACA improved insurance rates among justice-involved individuals with SUD.…”
Section: Introductionmentioning
confidence: 99%
“…13 Roughly half of justice-involved individuals are expected to be eligible for health insurance through the Affordable Care Act (ACA), 10,14 and many believe insurance expansion offers an opportunity to improve access to substance abuse and mental health treatment for this population. 5,14,15 One recent report suggested that the ACA improved insurance rates among justice-involved individuals with SUD. 16 However, to date, no national reports have assessed insurance trends among the general justice-involved population following implementation of either the ACA's dependent coverage mandate, which expanded parental health insurance to children age 19-25, 17,18 or Medicaid expansion and Marketplace plans.…”
Section: Introductionmentioning
confidence: 99%
“…The best estimates are that, in the 25 Medicaid expansion states and the District of Columbia, roughly 25% to 30% of persons released from jails could enroll in Medicaid, and in non-expansion states, 20% could enroll in Marketplace health plans (Regenstein & Rosenbaum, 2014). In some states, the estimates are even higher.…”
Section: The Changing Landscapementioning
confidence: 99%
“…A new study estimates that approximately one-fifth of all new enrollees within the Medicaid expansion group will be jail-involved. 1 The ACA also established parity for treatment of mental health and substance use disorders. As a result, for the first time, many low-income, childless adults are now eligible for not only health care coverage, but also coverage for their mental illnesses and substance use disorders.…”
Section: Potential Impacts Of the Affordable Care Act On The Jail-invmentioning
confidence: 99%
“…Members of this group tend to be young men of color, with high rates of poverty, low levels of education, and without health insurance coverage of any kind. 1 Jail-involved people also tend to be sicker than the general population, with high rates of chronic conditions, such as asthma, diabetes, and hypertension; communicable diseases, including HIV/ AIDS, tuberculosis, sexually transmitted diseases, and hepatitis B and C; mental illnesses; and substance use disorders. 2 Regardless of where they reside-whether in jail or in the community-it is important that these people receive appropriate health care.…”
mentioning
confidence: 99%